2015
DOI: 10.3390/life5021346
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Cyanobacterial Bloom Triggers in Missisquoi Bay, Lake Champlain, as Determined by Next-Generation Sequencing and Quantitative PCR

Abstract: Missisquoi Bay (MB) is a temperate eutrophic freshwater lake that frequently experiences toxic Microcystis-dominated cyanobacterial blooms. Non-point sources are responsible for the high concentrations of phosphorus and nitrogen in the bay. This study combined data from environmental parameters, E. coli counts, high-throughput sequencing of 16S rRNA gene amplicons, quantitative PCR (16S rRNA and mcyD genes) and toxin analyses to identify the main bloom-promoting factors. In 2009, nutrient concentrations correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 109 publications
1
23
0
Order By: Relevance
“…For example, cyanobacterial growth is optimal at higher temperatures, between 15 and 30°C (Konopka and Brock, 1978). We confirmed that cyanobacterial blooms are correlated with and likely respond to nutrient concentrations, as previously described (Fogg, 1969;Jacoby et al, 2000;Paerl and Huisman, 2008;Paerl and Huisman, 2009;Fortin et al 2015;Isles et al, 2015). Dissolved nitrogen and temperature were negatively correlated, which could be explained by the fact that the lake becomes enriched in nitrates during spring, when temperatures are lower and rain and drainage bring nutrients into the lake (Shade et al, 2007;Fortin et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, cyanobacterial growth is optimal at higher temperatures, between 15 and 30°C (Konopka and Brock, 1978). We confirmed that cyanobacterial blooms are correlated with and likely respond to nutrient concentrations, as previously described (Fogg, 1969;Jacoby et al, 2000;Paerl and Huisman, 2008;Paerl and Huisman, 2009;Fortin et al 2015;Isles et al, 2015). Dissolved nitrogen and temperature were negatively correlated, which could be explained by the fact that the lake becomes enriched in nitrates during spring, when temperatures are lower and rain and drainage bring nutrients into the lake (Shade et al, 2007;Fortin et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Between 50 and 250 ml of lake water was filtered depending on the density of the planktonic biomass using 0.2-μm hydrophilic polyethersulfone membranes (Millipore). Physico-chemical measurements, as described in Fortin et al (2015), were also taken during most sampling events . These environmental data included water temperature, average air temperature over one week, cumulative precipitation over one week, microcystin toxin concentration, total and dissolved nutrients (phosphorus and nitrogen).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular approaches outperform microscopy when estimating the diversity of heterotrophic prokaryotes and are increasingly applied to evaluate cyanobacterial community composition. The most widespread molecular methods for the study of aquatic microbiomes are denaturing gradient gel electrophoresis (DGGE) ( Shi et al, 2011 ; Li et al, 2012 ), terminal restriction fragment length polymorphism (T-RFLP) ( Chen et al, 2010 ; Li et al, 2011 ), Sanger sequencing of clone libraries ( Chen et al, 2010 ; Li et al, 2012 ; Cai and Kong, 2013 ), and more recently high-throughput sequencing ( Fortin et al, 2015 ; Zwirglmaier et al, 2015 ; Kurilkina et al, 2016 ; Lee et al, 2016 ; Berry et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The picocyanobacterium Synechococcus elongatus is of particular interest in this context because it is almost ubiquitously distributed (Stockner, Callieri, & Cronberg, 2002). The effect of Synechococcus on Microcystis gene expression is of ecological relevance since those cyanobacteria do not only co-occur (Fortin et al, 2015;Kolmonen, Sivonen, Rapala, & Haukka, 2004;Magana-Arachchi, Wanigatunge, & Liyanage, 2011;Ouellette, Handy, & Wilhelm, 2006;Zwart et al, 2005), but also can constitute the two most dominant cyanobacteria species in the phytoplankton community (Berry et al, 2016;Feng et al, 2016;Teneva, Mladenov, Belkinova, Dimitrova-Dyulgerova, & Dzhambazov, 2010;Ye et al, 2011).…”
mentioning
confidence: 99%